Piktogram Berbasis Design Thinking: Tingkatkan Pengalaman Pengunjung Pasar Jongke Surakarta - Lukitasari, Evelyne Henny; Rohhandoyo , Mozes Ardi; Fauzan , Mochammad Armand (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
Traditional markets are places for socializing, trading, and cultural exchange. They form the foundation of urban communities. The link between the market and local communities creates complexity and dynamics. However, a confusing signage system and layout problems lead to an unorganized market that is difficult for visitors to navigate. These issues show a need for a visual communication system that helps market visitors while showcasing the community's cultural values and identity. This study aims to understand and address the needs of market users by designing functional pictograms using the Design Thinking method. This process involves five phases: empathize, define, ideate, prototype, and test, including market managers, visitors, and traders. Testing with 50 visitors revealed that the new pictograms improved comprehension from an average of 58% to 88%. The time needed to interpret the symbols dropped from 7.2 seconds to 3.1 seconds. Qualitatively, this pictogram design blends local Surakarta cultural values, such as the parang motif and the sogan color, with modern geometric shapes like circles and rounded rectangles. This combination creates a friendly and easily recognizable look. The study concludes that applying Design Thinking is effective for creating a functional visual navigation system and for improving the visual identity of traditional markets. These markets can serve as inclusive public spaces that keep up with urban growth. The novelty of this research lies in merging a human-centered design approach with local cultural aesthetics. This can serve as a model for using visual communication design to revitalize traditional markets in Indonesia.